Chemotherapy with gemcitabine in patients with advanced gallbladder carcinoma - Teufel, Andreas; Lehnert, Thomas; Stremmel, Wolfgang; Rudi, Jochen (Zeitschrift für Gastroenterologie, 2000)
Advanced or metastatic gallbladder carcinoma is regarded not much sensitive to chemotherapy. Standard chemotherapy regimens have not been established up to now.
Gesehen am 19.11.2021